Oligomeric modeling and electrostatic analysis of the gp120 envelope glycoprotein of human immunodeficiency virus. - Kwong, P; Wyatt, R; Sattentau, Q; Sodroski, J; Hendrickson, W (2000)
The human immunodeficiency virus envelope glycoproteins, gp120 and gp41, function in cell entry by binding to CD4 and a chemokine receptor on the cell surface and orchestrating the direct fusion of the viral and target cell membranes. On the virion surface, three gp120 molecules associate noncovalently with the ectodomain of the gp41 trimer to form the envelope oligomer. Although an atomic-level structure of a monomeric gp120 core has been determined, the structure of the oligomer is unknown. Here, the orientation of gp120 in the oligomer is modeled by using quantifiable criteria of carbohydrate exposure, occlusion of conserved residues, and steric considerations with regard to the binding of the neutralizing antibody 17b. Applying similar modeling techniques to influenza virus hemagglutinin suggests a rotational accuracy for the oriented gp120 of better than 10 degrees. The model shows that CD4 binds obliquely, such that multiple CD4 molecules bound to the same oligomer have their membrane-spanning portions separated by at least 190 A. The chemokine receptor, in contrast, binds to a sterically restricted surface close to the trimer axis. Electrostatic analyses reveal a basic region which faces away from the virus, toward the target cell membrane, and is conserved on core gp120. The electrostatic potentials of this region are strongly influenced by the overall charge, but not the precise structure, of the third variable (V3) loop. This dependence on charge and not structure may make electrostatic interactions between this basic region and the cell difficult to target therapeutically and may also provide a means of viral escape from immune system surveillance.